Saúde mental no acolhimento residencial de crianças e jovens: prevalência, fatores de risco e fatores de proteção - Campos, Joana (2019)
The Residential Care is an extrafamilial promotion and protection measure that aims at placing the child or young person in the care of an entity which has the facilities and permanent equipment and a team of caregivers that guarantees you the care appropriate to their needs and provide them conditions that allow their education, welfare and integral development. In Portugal there are about 8000 children and young people who are in Residential Care, corresponding this number to 0.43% of children and adolescents Portuguese. Several studies have concluded that the prevalence rate and the severity of mental health problems is higher in children and young people institutionalized in relation to the general population. Risk factors for the problems observed are related not only with the family context previous to institutionalization, as well as individual characteristics and contextual variables from their centres. At the same time there is a significant number of clinical cases that are not promptly diagnosed, causing emotional and behavioral problems manifested reveal a risk factor for the psychopathology in adulthood. The main objective of this work focuses on the presentation of the state of the art regarding the prevalence of mental health problems in children and young people in Residential Care, as well as their risk factors and protective factors.